Pembelajaran New Normal: Perbedaan Kemampuan Berpikir Kreatif Berdasarkan Tingkatan Self-Regulated Learning Peserta Didik SMA - Refiyanti, Nur Alifa Deviar; Miatun, Asih (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
The focus of this research was to determine whether there were variations in the mathematics creative thinking abilities of students in class XI MIPA based on their level of self-regulated learning. A quantitative technique used in this research. This is an ex post facto research. This research included 159 students from MIPA class XI who completed a self-regulated learning questionnaire. The sample in this study was collected using the stratified random sampling approach, which was chosen based on high, moderate, and low levels of self-regulated learning. The sample for each level of self-regulated learning was determined using the sample-to-variable-ratio guidelines, which yielded up to 29 samples with a total of 87 students for each level. Data collection methods include self-regulated learning questionnaire and assessments of creative thinking abilities. The data analysis technique started with precondition tests, such as the normality test with the Kolmogorov-smirnov test and homogeneity test with the Barlett test, and then moved on to hypothesis testing with one-way ANOVA at a significance level of 5%, continued with post-ANOVA testing with the Scheffe test. Students with high self-regulated learning had higher creative thinking skills than students with moderate and low self-regulated learning, whereas students with moderate self-regulated learning had higher mathematical creative thinking skills than students with low self-regulated learning, according to the findings.